A Categorization Model of Requirements Based on Max‐Neef's Model of Human Needs. Issue 3 (31st July 2013) - Salado, Alejandro; Nilchiani, Roshanak
ABSTRACT Requirements categorization is an inherent part of the requirements engineering activity. Conventional approaches use a designer perspective (requirements organized according to design needs or attributes), a contractual perspective (requirements organized according to procurement or acquisition needs), or a combination of both. Such models present several inconveniences that result in limitation of system affordability: facilitate the generation of overlapping requirements, of design‐dependent requirements, and of a mix of requirements applicable to different levels of the architecture decomposition or to different products. The present research proposes a Need‐based Categorization (NbC) model that is system‐centric: Requirements are organized around the system. Inspired by Max‐Neef's model of human needs, the proposed model supports requirement elicitation by defining only what the system does, how well, where, and what it uses to accomplish it. The model facilitates the identification of constraints that limit the solution tradespace without supporting the satisfaction of new needs, of overlapping requirements, and of requirements that are not applicable to the system. Finally, the proposed model defines requirements in subsets that are associated with value to stakeholders, thus reflecting the actual dependency nature of requirements at a given level of an architecture decomposition, which promotes holistic decisions instead of local optimizations.